2011
DOI: 10.1109/tnet.2011.2130537
|View full text |Cite
|
Sign up to set email alerts
|

Touring DNS Open Houses for Trends and Configurations

Abstract: Abstract-DNS is a critical component of the Internet. It maps domain names to IP addresses and serves as a distributed database for various other applications, including mail, Web, and spam filtering. This paper examines DNS zones in the Internet for diversity, adoption rates of new technologies, and prevalence of configuration issues. To gather data, we sweep 60% of the Internet's domains in June -August 2007 for zone transfers. 6.6% of them allow us to transfer their complete information. Surprisingly, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…We return a single response, a CNAME, but rather than provide a host name in the response, we incorrectly provided an IP address. Such mistakes were found in a number of zones in previous work [Kalafut et al 2011]. …”
Section: Interactive Dns Resolver Profilingmentioning
confidence: 56%
See 1 more Smart Citation
“…We return a single response, a CNAME, but rather than provide a host name in the response, we incorrectly provided an IP address. Such mistakes were found in a number of zones in previous work [Kalafut et al 2011]. …”
Section: Interactive Dns Resolver Profilingmentioning
confidence: 56%
“…Our own prior work related to DNS [Kalafut et al 2011] investigated the contents of DNS zones and found some errors in their configurations. Prior work by Pappas et al [2009] investigated three specific configuration errors with potential impacts on DNS availability in greater detail.…”
Section: Related Workmentioning
confidence: 99%
“…Kalafut [4], attempted to transfer the zones listed in the .com and .net TLDs. They investigated zone transfer, zone diversity, deployment of new technologies and other configuration issues by downloading 6.6 % of zone file for second level domain names listed in .com and .net top-level domains.…”
Section: Related Workmentioning
confidence: 99%
“…One example is DNSSEC which helps to provide origin authentication and integrity assurances for the DNS messages [4]. A problem plaguing DNSSEC, and other Internet security features alike, is that it has a low adoption rate [8]. We attempt to overcome this by providing a simple, yet robust, system.…”
Section: Introductionmentioning
confidence: 99%